Experimental Gum Tapping of Jhingan in Uttar Pradesh - Singh, K. N.; Shukla, G. K. (Indian Forester, 1975)
Jhingan gum is mostly obtained from natural exudation and sometimes by tapping. The gum finds its use in Confectionary, Calico-Printing, preparation of interior varnishes, plastering, white washing etc. About 10,41,100 Jhingan trees of different diameter classes are estimated to spread over Tarai, Siwalik and Vindhyan tract of Uttar Pradesh. With a view to standardise the technique of tapping, Jhingan trees of different diameter classes were selected for tapping under local and notching methods. The trees were subjected to tapping under the two different methods and yield data were recorded Statistical analysis or the data reveal that there is no significant difference in yield of Jhingan gum whether the trees are tapped by local method or notching method. On combining the yield of gum for the two different methods and plotting average yield per tree against different diameter classes, a close scrutiny of the graph reveals that apart from a few random fluctuation, Jhingan trees of 40-50 cm diameter class yield more gum.